An all-sky search for R Coronae Borealis stars in ASAS-SN. Issue 4 (19th December 2018) - Shields, J V; Jayasinghe, T; Stanek, K Z; Kochanek, C S; Shappee, B J; Holoien, T W -S; Thompson, Todd A; Prieto, J L; Dong, Subo
ABSTRACT: We report the discovery of 19 new R Coronae Borealis (RCB) star and DY Per candidates with light curves from the All-Sky Automated Survey for Supernovae. We examined both an existing set of 1602 near/mid-infrared (IR) selected candidates and an additional 2615 candidates selected to have near/mid-IR spectral energy distributions consistent with those of known RCB stars. We visually inspected the light curves for the characteristic variability of these systems.